Trade and investment agreements for sustainable development? Lessons from the EU's Economic Partnership Agreement with the Caribbean - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2015)
The EU-CARIFORUM Economic Partnership Agreement signed in 2007 succeeded non-reciprocal trade preferences that had become incompatible with world trade law. As well as liberalising trade, the agreement pursues broader political goals: economic growth, poverty-reduction, closer regional integration in the Caribbean, and environmental concerns. Implementation is to be closely supported through aid for trade. The parties hope that this innovative approach will not only open up trade opportunities and contribute to sustainable development, but also ensure that adequate instruments, in the form of flexibilities and monitoring mechanisms, are provided to minimise risks. Critics fear that partial market opening by partner countries will cause dislocation of their local production. Now, after a number of years of experience with implementation, it is possible to review whether the agreement has succeeded in achieving its ambitious objectives, and whether it could serve as a model for further agreements between unequal trading partners. (SWP Research Paper)
Keywords: 320